Answer:
Below in bold.
Step-by-step explanation:
x^2 - y^2 = 11
2x^2 + y^2 = 97
From the first equation:
y^2 = x^2 - 11
Substituting in the second equation:
2x^2 + x^2 - 11 = 97
3x^2 = 108
x^2 = 36
x = 6, -6.
Substituting for x in the first equation:
(6)^2 - y^2 = 11
y^2 = 36 - 11 = 25
y = 5, -5.
<span>2x+ y = 3
x = 2y - 1
Make sure there are NO SPACES in your answer. Include a comma in your answer.
It looks like I could substitute the x=2y-1. Into 2x+y=3
2(2y-1)+y=3
4y-2+y=3
5y=5
y=1
x=2(1)-1
x=1
(1,1)
CHECK
2x+y=3
2(1)+(1)=3
2+1=3
3=3
Left hand side=Right hand side
Check other equation
x=2y-1
1=2(1)-1
1=1
Therefore the solution is (1,1). Since the left hand side= right hand side in each equation</span>
Answer:
Ok what you can try to do is multiply, then, subtract, add , or do division to see what you get. So try doing all of that then see what you're answer is.
Step-by-step explanation:
R=1 s=1 x=4 or you can basically double it and be like rs=2 x=8 i dont know your options or i could help better